Formulasi dan Evaluasi Sediaan Body Lotion Ekstrak Etanol Kulit Jeruk Manis (Citrus x aurantium L.) - Embun Larasati Kuncoro; Naswa Salsabila; Margaret Rianti Martalina; Renata Amalia Azizah; Zefanya Yoga Permana Purba (Lembaga Pengembangan Kinerja Dosen, 2026)
Sweet orange peel (Citrus x aurantium L.) is an agricultural by-product rich in bioactive compounds including flavonoids, phenolics, terpenoids, and vitamin C with antioxidant and moisturizing potential. This study aimed to formulate and evaluate a body lotion using 15% ethanol extract of sweet orange peel obtained by maceration with 96% ethanol. Evaluations included organoleptic, homogeneity, pH, adhesion, spreadability, viscosity, irritation, cycling test, cream type, and DPPH antioxidant activity assessments. The preparation was semisolid, yellow, with a characteristic herbal aroma, homogeneous, pH 8, adhesion time of 4.10 seconds, spreadability of 9.9–11.1 cm, and acceptable viscosity. The preparation caused no skin irritation, remained stable through six cycling test cycles, and formed an oil-in-water (O/W) emulsion. Antioxidant activity showed an IC₅₀ of 284.6 ppm (weak category) compared to vitamin C as positive control (IC₅₀ 4.2 ppm). It was concluded that ethanol extract of sweet orange peel can be formulated into a stable and safe body lotion, though further optimization is needed to enhance its antioxidant activity.